Estimasi Tingkat Keparahan Kebakaran Hutan dan Lahan di Kabupaten Muaro Jambi Provinsi Jambi Tahun 2024: Estimated Severity Level of Forest and Land Fires in Muaro Jambi District, Jambi Province in 2024 - Nur Syahira, Talitha; Saharjo, Bambang Hero; Nurhayati, Ati Dwi (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Muaro Jambi District is a district in Jambi Province that often experiences forest and land fires. The study aims to analyze the distribution of hotspots and their relationship with rainfall and estimate the severity of forest and land fires in Muaro Jambi District in 2024. The sources used were hotspot distribution data from the VIIRS sensor, monthly rainfall, and Sentinel-2 images. The results showed that the number of hotspot increased in July and reached its peak in September. The number of hotspots and rainfall have an inversely proportional relationship. Estimation of the severity of forest and land fires in Muaro Jambi District in 2024 based on the NBR (Normalized Burn Ratio) index from the Sentinel-2 image shows that most of the forest and land fire areas are at a moderate severity level, namely 61.45% with an area of 869.53 ha.